Bridging the Vaccination Equity Gap: A Community-Driven Approach to Reduce Vaccine Inequities in Polio High-Risk Areas of Pakistan - Imran A. Chauhadry; Sajid Bashir Soofi; Muhammad Sajid; Rafey Ali; Ahmad Khan; Syeda Kanza Naqvi; Imtiaz Hussain; Muhammad Umer; Zulfiqar A. Bhutta (Vaccines)
Background: Immunization saves millions of lives, and globally, vaccines have significantly contributed to reducing mortality and morbidity due to more than 20 life-threatening illnesses. However, there are considerable disparities in vaccination coverage among countries and within populations. This study evaluates the reduction in disparities in vaccination coverage across various socio-economic groups by adopting an integrated community-engagement approach combined with maternal and child health services through mobile health camps. Methods: This secondary analysis is based on a community-based demonstration project conducted between 2014 and 2016 across 146 union councils in polio high-risk districts of Sindh, Khyber Pakhtunkhwa (KP) and Baluchistan in Pakistan. The intervention involved structured community engagement and mobile health camps providing routine immunization alongside maternal and child health services. Data were collected through cross-sectional independent surveys using the WHO two-stage cluster technique at the baseline and the endline, covering over 120,000 children under 5 years old. Four key outcome indicators were analyzed: fully vaccinated children, under-immunized children, unvaccinated children, and polio zero-dose children for equity in vaccine uptake. Results: The proportion of fully vaccinated children increased in the lowest wealth quintile from 28.5% (26.7%, 30.3%) at the baseline to 51.6% (49.5%, 53.8%) at the endline. In comparison, the increase in the richest quantities was 16.2% (14.0%, 18.4%) from the baseline 56.4% (54.6%, 58.2%) to the endline 72.7% (71.1%, 74.2%). Under-vaccination dropped by 10.2% (95% CI: −11.4%, −9.1%), with the poorest quintile showing an 11.8% reduction. The gap between the highest and lowest wealth quintiles in full immunization narrowed by 6.9%, from 27.9% to 21.0% at the baseline and the endline, respectively. The prevalence of zero-dose children significantly decreased across all quintiles, with the highest reduction observed in the lowest quintile of −11.3% (−13.6%, −9.1%). The difference between the highest and lowest wealth quintiles reduced from 6.2% to 3.8%. A significant reduction in polio zero-dose children was achieved, as 13.5% (95% CI: −14.8%, −12.2%), from 29.2% (95% CI: 28.0%, 30.3%) to 15.6% (14.8%, 16.5%). Conclusions: This study shows that integrating community engagement with maternal and child health services through health camps can significantly enhance immunization coverage and reduce wealth-based disparities in high-risk, hard-to-reach areas. The approach improved coverage for zero-dose and fully vaccinated children, suggesting a potential for scaling in regions with access issues, conflict, and vaccine hesitancy.